(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Currently, the search of novel phytochemicals with unique biological potentialities is a pre-requisite for the designing ideal drugs for the human kind. Sea weeds are bioresources with a broad spectrum of medicinal properties with minimal side effects. Kerala, the Southern state of India reported high incidence of Chikungunya virus (CHIKV) infections in the last several tears. No specific virucidal therapy or effective vaccines are available. This emphasizes the need of searching for phytochemicals as drugs with less cost and more effective. Therefore, an attempt was made in screening purified terpenoid extracts of selected sea weeds as anti-CHIKV potential. In this study the terpenoids composition from the red algae Hypnea musciformis, Kappaphycus alvarezii and Gracillaria dura were identified and analyzed by thin layer chromatography and Gas chromatography- Mass spectrum. The methanolic extract of seaweeds was purified by column chromatography and each fraction was eluted by using petroleum ether and ethyl acetate as solvent combination. The analysis of the purified fraction of H. musciformis and K. alvarezii revealed the presence of 8 terpenoid fractions, and G. dura showed only 4 major components respectively. Vero cell lines were employed in the antiviral assays, infected to CHIKV, and treated with varied doses of purified terpenoid extracts. In the antiviral activity, terpenoid extracts of G. dura showed remarkable and promising EC50 inhibitory effect at 1.25 μg/ml. Further, the terpenoid extracts displayed efficient virucidal activity against CHIKV (inhibit around 90%) with 5 μg/ml dosage. As the last phase, terpenoid extracts added at time intervals of 0, 1, 2, 3 post-infection periods still maintained a significant inhibitory potential against CHIKV viral replication. Thus, the overall study suggests that the terpenoid extracts of G. dura may be effectively used in the prevention and treatment of CHIKV infections. Clinical studies may be warranted for designing a promising new anti-CHIKV drug.